Autosomal dominant Kufs disease in a Georgian adult woman: A case report - Nikoloz Papiashvili; Sopio Gagua; Nana Gonjilashvili; Natela Okujava; Aleksandre Tsereteli (Epilepsy & Behavior Reports, 2025)
Progressive myoclonic epilepsies (PMEs) are a diverse group of neurodegenerative disorders characterized by myoclonus, seizures, and progressive cognitive and motor decline. This report presents a case of a subtype of PME, autosomal dominant Kufs disease (NCL type 4) documented for the first time outside of North America or Western Europe. The patient had a six-year history of progressive epilepsy that was resistant to pharmacotherapy, followed by myoclonus, cerebellar dysfunction, and cognitive deterioration. The patient’s family history revealed a similar syndrome in the mother, who passed away seven years after the onset of the disease. Genetic testing identified the heterozygous pathogenic variant NM_025219.2:c.344T > G (p.Leu115Arg) in the DNAJC5 gene. This case report broadens the geographic distribution of NCL type 4 and calls attention to the multifaceted diagnostic challenges posed by the condition.